2020
DOI: 10.3390/plants9020153
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Eutectic Solvents for the Extraction of Rutin and Rosmarinic Acid from Satureja montana L. and Evaluation of the Extracts Antiradical Activity

Abstract: Satureja montana L. was used in the current research as the plant exhibits numerous health-promoting benefits due to its specific chemical composition. The extraction method based on deep eutectic solvents (DESs) was used for the extraction of rutin and rosmarinic acid from this plant. Five different choline chloride-based DESs with different volumes of water (10%, 30%, and 50% (v/v)) were used for the extraction at different temperatures (30, 50, and 70 °C) to investigate the influence on rosmarinic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…The obtained results are partly in line with the published studies earlier [ 2 , 9 , 30 ]. Kremer et al [ 9 ] identified six phenolic compounds (rutin, quercetin, p -coumaric, ellagic, rosmarinic and syringic acids) using HPLC in methanolic and ethanolic extracts of S. montana.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The obtained results are partly in line with the published studies earlier [ 2 , 9 , 30 ]. Kremer et al [ 9 ] identified six phenolic compounds (rutin, quercetin, p -coumaric, ellagic, rosmarinic and syringic acids) using HPLC in methanolic and ethanolic extracts of S. montana.…”
Section: Resultssupporting
confidence: 93%
“…López-Cobo et al and Jakovljević et al showed that water, ethanol in different concentrations 30%, 50%, 70%, and methanol extracted phenolic acids and flavonoids in the form of aglycons and glycosides. Moreover, the extent of the extraction depends on a solvent, its concentration, temperature, nature of a phenolic compound [ 28 , 30 ]. Furthermore, different authors differ in their opinions on an optimal solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the addition of water to the DES/NADES system should be done with caution, as a large excess of water could break the hydrogen bonds between the components and thus lose the eutectic properties of the solvent produced [78]. This is probably the reason why researchers have focused on optimizing the addition of water in the extraction process, usually by testing a content between 0% and 70% [68,71,[79][80][81]. In most of these studies a water content between 20% and 40% was determined as the optimum.…”
Section: Short Historical Overview Of Development and Use Of Des/nadesmentioning
confidence: 99%